Language Style Operated by Indonesian Minister of Education to Urge Indonesians to Learn from Covid-19 Pandemic as Character Leadership Value - Chalimah Chalimah; Ainiyah Mahmudah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2022)
Language style is operated to convey ideas and thoughts as well as to express intentions and to show who the speakers themselves. In the era of glory for You-tube, this research focuses on categorizing the language style used by the Indonesian Minister of Education in Najwa program uploaded in Najwa You-tube channel. The researcher used qualitative research to analyze and describe language style used in the transcript of video interview and document analysis. The data of this research is in the form of utterances. The data analysis technique was obtained through qualitative analysis by doing three steps; organizing and familiarizing, coding and reducing, and interpreting and representing. Researchers only found 3 styles, namely: casual style, intimate style and consultative. This research gives contribution in learning the character leadership shown by the Indonesian Minister of Education.